Individual Educational Programs as New Mechanism of Integration between Higher Education and Labor Sphere - Vasiliy S Senashenko; Elena P Struchkova (Peoples' Friendship University of Russia (RUDN University), 2019)
At present the problem of the integration between the higher education and the sphere of labor has become particularly urgent. It is noted that the attempts earlier made by a number of authors to solve the problem of the integration between the higher education and the labor sphere by combining educational and professional standards, as well as by harmonizing the requirements of the labor market for the qualiﬁcations of specialists and the competencies of graduates of higher education are facing signiﬁcant diﬃculties. In this paper, we consider individual educational programs as one of the mechanisms of combining the higher education and labor. The analysis of the emerging diﬀerences between the higher education and the sphere of labor in the context of diﬀerent educational models has been conducted. Thus, for example, within the framework of the professional model of the educational process organization, the possibilities of building individual educational programs are limited by the amount of labor intensity of the variable part of the educational program according to the ﬁeld of study or subject specialism. At the same time, we are talking about professional individual educational programs, which are based on the processes of the formation of professional subjectivity of the student and the formation of his/her professional image. Such individual educational programs not only orient students on a certain type of work activity already at university, but also guarantee a well-grounded choice of the future profession. The paper focuses on the signiﬁcant impact of the individualization of professional and professionalization of individual educational programs, as well as the multilevel structure of higher education on the nature of the integration of educational programs of higher education and the trajectories of professional development of young professionals. It is emphasized that the adaptation of students to the educational process, built on the principles of individualization of educational programs, is a key point of interdisciplinary psychological and pedagogical problems of the development of creative abilities of students and is accompanied by the mastery of new skills.